2021
DOI: 10.1021/acs.iecr.1c00967
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Compressed Woody Biomass: Correlating Rheology and Microcompounder Measurements

Abstract: Transport of milled solid biomass can be problematic in biomass conversion processes due to the material’s high cohesiveness, low bulk density, and poor flowability. Here, the goal is to investigate the flow behavior of compressed biomass under conditions similar to compression-screw feeders. To mimic the flow of woody biomass inside a compression-screw feeder, two lignocellulosic biomass feedstocks were fed to a co-rotating twin-screw microcompounder. Force and screw speed from the microcompounder were correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In a similar system, the stable β polymorph formed with slow cooling for a sample of lard (Campos et al, 2002; Mohanan et al, 2015). At faster cooling rate of 1°C/min, the viscosity increase at lower temperatures because the crystals do not have time to develop their structure and network (Fakhrabadi et al, 2021; Mohanan et al, 2015). We hypothesis that additional time leads to the formation of larger and more stable crystals.…”
Section: Flow Behavior Of Pure Fames and Binary Mixturesmentioning
confidence: 99%
“…In a similar system, the stable β polymorph formed with slow cooling for a sample of lard (Campos et al, 2002; Mohanan et al, 2015). At faster cooling rate of 1°C/min, the viscosity increase at lower temperatures because the crystals do not have time to develop their structure and network (Fakhrabadi et al, 2021; Mohanan et al, 2015). We hypothesis that additional time leads to the formation of larger and more stable crystals.…”
Section: Flow Behavior Of Pure Fames and Binary Mixturesmentioning
confidence: 99%
“…Excessive moisture content could create an ideal environment for microbial growth and enzyme activity (Zheng et al 2011), leading to the decay and degradation of forage blocks (Tumuluru et al 2011). Additionally, it reduces the adhesive strength between particles, thereby weakening the overall structural integrity of the forage blocks (Akbari et al 2021). During the production of alfalfa feed blocks, it had been observed that as the moisture content increases within the range of 15% to 25%, the density of the formed blocks decreased (Du 2023).…”
Section: Introductionmentioning
confidence: 99%